MEDIATION OF ATLAS IN THE EFFECT OF AUDIT EXPERIENCE AND COMPETENCE ON AUDIT RISK - Fibriani, Rudiana; Q, Arief Nurdiannova; Hidayat, Ujang Syaiful (Universitas 17 Agustus 1945 Surabaya, 2023)
In conducting an audit, the auditor must pay attention to audit risk in order to provide an accurate opinion on the financial statements. Currently, ATLAS is used in financial statement audits to improve the quality of auditors' work. This quantitative research using the SEM-PLS method aims to determine whether ATLAS is also able to mitigate audit risk and see whether the auditor's experience and competence factors can support the use of ATLAS, and whether ATLAS mediates the effect of auditor experience and competence on audit risk. The research respondents were 31 KAPs in Surabaya. The results found that Audit Experience, Competence and ATLAS have an influence on ATLAS but both have a negative effect on Audit Risk, while ATLAS mediates the negative effect of Audit Experience and Competence on Audit Risk.